From estimation resultsto stylized facts: Twelve recommendations for empirical research in international activities of heterogeneous firms - Joachim Wagner (Institute for the Study of Labor (IZA), 2010)
Heterogeneous firms are at the heart of both the New New International Trade Theory and the Micro-econometrics of International Firm Activities. One important aim of microeconometric studies is to uncover stylized facts that hold over space and time, and that can both inspire theoretical models that are based on realistic assumptions, and inform policy debates in an evidence-based way. Which results from the thousands of empirical estimates reported in the literature on the micro-econometrics of international firm activities do we consider as convincing? Based on my own experience from the last twenty years I use the opportunity of this lecture to make twelve recommendations that, hopefully, will help to find the right way on the thorny road from estimation results to stylized facts. I will deal with the following topics: comparisons of means vs. comparisons of distributions; extremely different firms, or outliers; unobserved heterogeneity; simultaneous occurrence of differences across quantiles, outliers, and unobserved heterogeneity; heterogeneous effects of international firm activities on firm performance; replication; within-study replication by international research teams; meta-analysis; and talking to practitioners.
Keywords: F14; C21; C23; 330; international firm activities; heterogeneous firms; stylized facts; robust statistics; replication; meta anaysis; Multinationales Unternehmen; Unternehmensentwicklung; Empirische Methode; Mikroökonometrie; Meta-Analyse; Welt